Assessing the Role of Women Empowerment in Disaster Management in Pakistan - Afsheen, Arshad (2024)
This research examines the relationship between women empowerment and disaster management in the context of Pakistan, focusing on the research questions related to the limited involvement of women in disaster response initiatives because of social, educational, and economic constraints in the country. The study seeks to identify how these barriers affect the contributions of women in disaster risk reduction, response and recovery. The research embraces a qualitative research design, and the main data collection techniques include focus group discussions, semi-structured interviews, and policy documents review. This paper uses Bult’s conceptual model to analyse the processes, dimensions, and interventions that are required to achieve women’s empowerment at the individual, community and institutional levels. The relevance of the model is that it offers a multiple perspective approach for incorporating gender related approaches onto disaster management policies. Thus, the study reveals that the major barriers, including limited mobility, gender stereotype, lack of education and training, and limited access to financial resources, limit women’s participation in disaster management. It is important to note that these findings are similar and replicated in all the data sources used, meaning that these barriers are persistent. A major strength of the study is that the findings provide practical implementation strategies for enhancing the involvement of women in disaster management. It highlights capacity development, raising community awareness, and the integration of gender-responsive strategies in disaster response plans as critical measures for addressing disaster risks. The study also aims at highlighting the positive effects associated with women empowerment including better early warning mechanisms, efficient relief operations, and harmonious social relations. Pursuant to the limitations,the study concentrated on specific areas and excluded quantitative information which could have been useful. Further research should focus on whether such policies remain sustainable and feasible in the long run and on how the applicability of the suggested measures depends on cultural and geographical differences.